Initial development of watermelon in fuction of substrates and irrigation with saline water - Carreiro, Daniel de Almeida; Silva, Igor Marcos Almeida da; Lobo, Jackson Teixeira; Lino, Jaynne de Oliveira Siqueira; Fatima, Reynaldo Teodoro de; Sanches, Luciana Guimarães; Santos, Alana Juliete da Silva; Mudo, Laiane Eugênia Delmondes (Scientia Plena, 2020)
We evaluated the initial development of watermelon cv. Crimson Sweet seedlings grown in different organic substrates and electrical conductivity of irrigation water. The experiment was carried out in a greenhouse between January and March of 2017. The experimental design was in randomized blocks with factorial arrangement 3 x 5. The treatments were combinations of three substrates: soil + bovine manure (SBM) (1:1); soil + sheep manure (SSM) (1:1) and commercial substrate Basaplant® (CS), and five electrical conductivity of irrigation water (ECiw): C1 – 0.3 dS m-1; C2 – 1.5 dS m-1; C3 – 2.7 dS m-1; C4 – 3.9 dS m-1 and C5 – 5.1 dS m-1. Plant height, number of leaves, stem diameter, root fresh mass, stem fresh mass, leaf fresh mass, root dry mass, stem dry mass, and leaf dry mass were evaluated at 37 days after sowing (DAS). The interaction between substrate x ECiw significantly affected the variables plant height, number of leaves, stem fresh mass and leaf fresh mass; all the analyzed variables were affected by substrate factor, while plant height, number of leaves, root dry mass, stem dry mass, and leaf dry mass were affected by ECiw. It is possible to produce watermelon cv. Crimson Sweet seedlings using water with electrical conductivity up to 2.86 dS m-1 associated with commercial substrate and up to 2.67 dS m-1 associated with sheep manure. It can be inferred that the use of commercial substrate is more suitable for the production of watermelon cv. Crimson Sweet seedlings.